Postoperative pulmonary edema secondary to rapid fluid injection into the corporal bodies during surgical correction of penile curvature: a rare consequence of artificial erection - Grober, Ethan D.; Shin, Eyun-Jung (Canadian Urological Association Journal, 2013)
Some experts contend that occlusion of the proximal corpora cavernosal bodies of the penis with a tourniquet or manual compression during induction of an artificial erection distorts the penile anatomy and potentially masks proximal curvatures. The current report highlights a rare, but potentially morbid, case of postoperative pulmonary edema as a consequence of rapid fluid injection into the corporal bodies during surgical correction of penile curvature, in a 48-year-old male with a high-risk cardiac history.